Dental neglect among children in Chennai - Deepa Gurunathan; Arunachalam Karthikeyan Shanmugaavel (Wolters Kluwer Medknow Publications, 2016)
Background: Child dental neglect is the failure of a parent or guardian to meet the child's basic oral health needs such that the child enjoys adequate function and freedom from pain and infection, where reasonable resources are available to family or caregiver. Aim: The aim of the study is to evaluate the phenomenon of dental neglect among children in Chennai and to associate dental neglect with oral health status of children aged 3-12 years. Materials and Methods: This is a cross-sectional study involving 478 pairs of parents and children. Dental neglect scale and a questionnaire were used to assess the dental neglect score among parents of the children involved in the study. Oral health status of children was clinically assessed using oral hygiene index, decayed, extracted, filled teeth (def(t)), pulp, ulcers, fistula, abscess (pufa), decayed, missing, filled teeth (DMFT), PUFA as per the World Health Organization criteria and pufa/PUFA index. Student's t-test and one-way ANOVA were used appropriately for statistical analysis using SPSS software version 20.0. Results: A significant higher dental neglect score was reported among the parents who reside in the suburban location (P < 0.001), whose educational qualification was secondary (P < 0.001) and who have not availed any dental service for >3 years (P = 0.001). A significant higher DMFT (P = 0.003), deft (P = 0 < 0.001), pufa (P = 0.011), and debris index (P = 0.002) scores were seen in the higher dental neglect group. Conclusion: Child dental neglect is seen among the parents whose educational qualification was secondary, who reside in the suburban location, and who have not utilized the dental services for more than 3 years in Chennai. This dental neglect results in poorer oral health of children.